Factors affecting the efficacy of small bowel capsule endoscopy in patients with chronic abdominal pain - He, Xinlong; Xu, Qing; Xue, Hanbing (Frontiers in Medicine, 2025)
BackgroundAbdominal pain is a common clinical symptom, and the role of small bowel capsule endoscopy (SBCE) in the evaluation of abdominal pain remains a subject of ongoing debate. The objective of this study is to investigate the factors influencing the efficacy of SBCE in patients with chronic abdominal pain.MethodsThis study retrospectively analyzed the medical records of patients presenting with chronic abdominal pain as the primary complaint who underwent SBCE at Renji Hospital from January 2014 and January 2023. Data collection included patient demographics and relevant influencing factors, such as hospitalization status, anemia, elevated inflammatory markers, hypertension, and diabetes. Univariate and multivariate analyses were employed to examine the factors associated with SBCE transit status and positive outcomes.ResultsA total of 524 patients were included in the study, of whom 113 presented with DUGT and received conservative observation, pharmacological treatment, or endoscopic intervention as appropriate. The overall completion rate was 97.1%. Hospitalization status, diabetes, and anemia were identified as risk factors for DUGT in multivariate analyses. Positive lesions were detected in 160 cases, yielding an overall lesion detection rate of 30.5%. Furthermore, multivariate regression analysis indicated that anemia (hemoglobin <90 g/L) and elevated inflammatory markers were associated with a higher rate of positivity.ConclusionIn conclusion, our study found that hospitalization status, diabetes, and anemia as significant risk factors for DUGT in patients with chronic abdominal pain. Furthermore, we found that SBCE is highly effective in detecting lesions in patients with chronic abdominal pain combined with anemia and elevated inflammatory markers.